2005
DOI: 10.1128/iai.73.7.4112-4118.2005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pregnancy and Intensity of Plasmodium falciparum Transmission on Immunoglobulin G Subclass Responses to Variant Surface Antigens

Abstract: Placenta-sequestering Plasmodium falciparum involved in the pathogenesis of pregnancy-associated malaria (PAM) in otherwise clinically immune women expresses particular variant surface antigens (VSA PAM ) on the surface of infected erythrocytes that differ from VSA found in parasitized nonpregnant individuals (non-PAM type VSA). We studied levels of immunoglobulin G (IgG) and IgG subclasses with specificity for VSA PAM and for non-PAM type VSA in pregnant and nonpregnant women from two sites with different end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
49
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 30 publications
15
49
0
Order By: Relevance
“…Antibody responses to a crude P. falciparum blood stage extract in parturient women were predominantly cytophilic given the higher levels and prevalence rates of IgG1 and IgG3 subclasses seen relative to IgG2 and IgG4. These findings are in accordance with reports from previous studies 13,15,20 . Similarly, VSAPAM -specific IgG subclass responses in pregnancy are dominated by IgG1 and IgG3 antibodies as reported by Megnekou et al 13 and Eliott et al 15 .…”
Section: <0001supporting
confidence: 83%
See 2 more Smart Citations
“…Antibody responses to a crude P. falciparum blood stage extract in parturient women were predominantly cytophilic given the higher levels and prevalence rates of IgG1 and IgG3 subclasses seen relative to IgG2 and IgG4. These findings are in accordance with reports from previous studies 13,15,20 . Similarly, VSAPAM -specific IgG subclass responses in pregnancy are dominated by IgG1 and IgG3 antibodies as reported by Megnekou et al 13 and Eliott et al 15 .…”
Section: <0001supporting
confidence: 83%
“…These findings are in accordance with reports from previous studies 13,15,20 . Similarly, VSAPAM -specific IgG subclass responses in pregnancy are dominated by IgG1 and IgG3 antibodies as reported by Megnekou et al 13 and Eliott et al 15 . Cytophilic antibodies are usually produced together 15 .…”
Section: <0001supporting
confidence: 83%
See 1 more Smart Citation
“…However, as cytophilic antibodies have been collected from infected pregnant women (39), it should be borne in mind that other antibodydependent mechanisms, such as phagocytosis and complement activation, may also help to protect against PAM, in addition to blocking adhesion. Consistent with the existence of additional antibody mechanisms, Megnekou et al (40) showed that IgG1 and IgG3 were the most prevalent subclasses of PAM antibodies in Cameroonian women, and that larger amounts of these antibodies were found in pregnant multiparous women.…”
Section: Does the Antibody-mediated Immune Response Play A Role In Pam?mentioning
confidence: 73%
“…Moreover, levels of IgG antibodies against CS2 were increased in women with qPCR-positive P. falciparum infection at delivery. 16,17 These results indicate a close relationship between antibody levels and the intensity of malaria transmission [16][17][18][34][35][36] and suggest that antibodies against VAR2CSA may be a marker for cumulative exposure to the parasite during pregnancy. 19 More important, this study shows that 5 years of a marked decline in the prevalence of malaria was accompanied by reductions in levels of IgG antibodies against CS2 parasites by a factor of 2.8 and by reductions in IgG antibodies against antigens that are not specific to pregnancy, as well as by an increase in the geometric mean of parasite densities and a larger adverse effect of these infections on maternal hemoglobin levels and the weight of newborns.…”
Section: Antimalarial Immunitymentioning
confidence: 99%